The number of muscarinic receptors in chick amnion muscle - Cuthbert, A. W. (1973)
1. [(3)H]-Propyl benzilylcholine mustard ([(3)H]-PrBCM) an irreversible specific antagonist of muscarinic acetylcholine receptors, has been used to label the muscarinic receptors in the aneuronal muscle of isolated 11 day amniotic membranes of chick embryos. 2. This muscle was found to have about 9 fmol/mg dry weight of receptor material. This is only 1-2% of the amount found in intestinal muscle. 3. Pharmacological studies with isolated amniotic membranes using PrBCM show that labelling is to functional receptors and that the receptor reserve is small. 4. The significance of the difference in receptor reserve in innervated and aneuronal plain muscle is discussed.